Аналіз застосунків для ведення обліку персональних фінансів - Краснянська, В. В. (ХНУРЕ, 2025)
The article explores popular applications for personal finance management, analyzing their key features, advantages, and drawbacks. It highlights different approaches to budgeting, including envelope-based systems, automated financial analysis, forecasting future incomes and expenses, as well as manual expense tracking and categorization. The article concludes that each application suits different user needs, emphasizing the importance of choosing a tool based on individual financial habits.
Keywords: облік персональних фінансів; персональні фінанси